Communication of members of the health team with the patient during preoperative preparation - Ignjatović Marija; Kekuš Divna (Association of Nurses Technicians and Midwives, 2019)
INTRODUCTION: Communication in nursing practice represents one of the basic skill during healthcare services. With continuity, showing concern and interest for the patient, a thrustworthy relationship is built, which contributes to better cooperation and to a more positive outcome of the whole treatment. During the preoperational preparations, nurse is conducting an informational and theraperutical communication through all the phases of healthcare and treatment. In everyday nursing, communication takes place in many relationships. Besides the successfull communication with the patient, a good cooperation between all the members of the health team is indispensable and equally important. AIM: To examine the communication efficency of members in the health team with the patient in preoperative preparation. Materials & methods: The study included 55 operated patients who underwent all elements of preoperative preparation. A questionnaire, specially created for this purpose, was used as a data collection instrument. The survey was conducted anonymously, and each respondent signed a voluntary informed consent. RESULTS: Most patients are very satisfied with all the information they have received on the disease, care, treatment and planned interventions. More than half of the patients felt that there were no aggravating factors in communication with the medical staff, while 1/5 of the respondents felt that the medical staff did not have enough time to communicate with the patients. The patient rating for communication with physicians was 4.87 and for communication with nurses 4.82. CONCLUSION: Communication between health team members and patients while preparing for surgery is of high quality and contributes to good collaboration, greater satisfaction and a more positive outcome.